The economic value used to stimulate the development of enterprise structures in the R & D system mechanisms - A. O. Ryzhkov (Путеводитель предпринимателя)
This article examines the economic value used to stimulate the development of enterprise structures in the R & D system mechanisms. The analysis of innovative activity of enterprise structures, deals with the problems limiting the process of innovation. It is a comparative analysis of the impact of the direct and indirect stimulation of development of enterprise structures in the R & D system.